Diversidade e estrutura da nematofauna em regiões estuarinas tropicais (~7°S) - Silva, Sebastião Tilbert Ângelo da (2017)
General abstract The meiofauna is constituted by microscopic organisms ranging from 44 and 500 µm in length. Nematoda are highly diversified and abundant and very important from both the ecological and biomonitoring points of view. This study aimed to describe the nematofauna diversity from Mamanguape River (ERM) and Paraíba River (ERPB) estuaries (Chap. 1) and analyze their seasonal and spatial distribution at the ERM (Chap. 2) and relationships with environmental variables. From a total of 72 samples, 79 genera were found, 60 in the ERM (one of the highest diversities recorded from estuaries) and 53 to the ERPB, with Terschellingia, Daptonema, Sabatieria, Gomphionema, Pseudolella and Perepsilonema dominating. The diversity was high; however the estimators suggest even higher diversities, >60 and >90 for ERM and ERPB respectively. The analysis of more than 120 animals on each sample for the taxonomic study possible would result in higher richness, considering the higher diversity suggested by the diversity estimators along with the great quantity of rare genera. The ecological study at ERM (Chap. 2) found higher abundances in the dry season and a meiofauna assemblage greatly dominated by nematodes. Both meiofaunal and nematofaunal assemblages were highly related to the granulometry and organic matter. The ecological indexes showed higher eutrophication in the rainy season, particularly in the entrance of the estuary north margin. The dominant genera were mostly composed by juveniles. This study contributed significantly to the meiobenthology providing important data to the knowledge of the nematofaunal biodiversity and ecology, with direct implications in the environmental biomonitoring and for future researches.